Strategi Pembelajaran Melalui Metode Demonstrasi Dalam Upaya Mengembangkan Kreativitas Anak - Rana riendawati Mooy; Gloria Gabriel Lumingas; Reni Triposa (Philoxenia: Jurnal Teologi dan Pendidikan Kristiani, 2024)
This study aims to analyse learning strategies through demonstration method in developing children's creativity. The demonstration method was chosen because of the ability of students to convey concepts visually and practically, making it easier for them to understand what the teacher has given. This research uses a descriptive qualitative method conducted in the classroom by involving various activities that encourage exploration and active participation in the classroom. The results showed that the application of this method significantly improved children's creativity, as seen from the increase in critical thinking, innovation, and self-expression. The findings indicate that the demonstration method can be an effective tool in the learning process to stimulate children's creativity.